2006
DOI: 10.1182/blood-2005-06-2547
|View full text |Cite
|
Sign up to set email alerts
|

Variable phosphorylation states of pigment-epithelium–derived factor differentially regulate its function

Abstract: The pigment epithelium-derived factor (PEDF) belongs to the family of noninhibitory serpins. Although originally identified in the eye, PEDF is widely expressed in other body regions including the plasma. This factor can act either as a neurotrophic or as an antiangiogenic factor, and we previously showed that the 2 effects of PEDF are regulated through phosphorylation by PKA and CK2. Here, we studied the interplay between the PKA and CK2 phosphorylation of PEDF, and found that a PEDF mutant mimicking the CK2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…It was also shown that PDGF, the other growth factor implicated in angiogenesis, is phosphorylated by CK2. The CK2 phosphorylated form of PDGF has an elevated anti-angiogenic activity [48,49]. Recently, it turned out that PDG induced the CK2a' subunit expression [50].…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that PDGF, the other growth factor implicated in angiogenesis, is phosphorylated by CK2. The CK2 phosphorylated form of PDGF has an elevated anti-angiogenic activity [48,49]. Recently, it turned out that PDG induced the CK2a' subunit expression [50].…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…PEDF phosphorylated by CK2 exhibited a strong anti-angiogenic activity [49]. Most of these experiments were performed with glutamic acid mutants, which mimic CK2 phosphorylation indicating that a negative charge at the CK2 phosphorylation sites is sufficient for the anti-angiogenic activity.…”
Section: Ck2 and Angiogenesismentioning
confidence: 99%
“…PEDF undergoes N-glycosylation that occurs at the Asn285 site. In addition, Maik-Rachline et al (2005) demonstrated that PEDF is a phosphoprotein, which has several phosphorylation sites that determine its function as either neurotrophic or anti-angiogenic (Maik-Rachline & Seger 2006). The neurotrophic activity is mediated by PKA that phosphorylates PEDF on Ser 227, whereas the anti-angiogenic activity is mediated by CK2 that phosphorylates PEDF on Ser 24 and Ser 114.…”
Section: Pedf Post-translational Modificationsmentioning
confidence: 99%
“…The neurotrophic activity is mediated by PKA that phosphorylates PEDF on Ser 227, whereas the anti-angiogenic activity is mediated by CK2 that phosphorylates PEDF on Ser 24 and Ser 114. In addition, induction of PKA followed by CK2 phosphorylation exhibits its most potent anti-angiogenic and neurotrophic activities (Maik-Rachline & Seger 2006). On top of its neurotrophic and anti-angiogenic activities (Simonovic et al 2001), PEDF was shown to function as an anti-inflammatory (Wang et al 2008) and anti-oxidative factor (Yamagishi et al 2005, Bar-Joseph et al 2014.…”
Section: Pedf Post-translational Modificationsmentioning
confidence: 99%
“…2 It is ubiquitous in humans and is functionally involved in biological processes such as antiangiogenesis, endothelial cell migration and inhibition of differentiation of tumour and neural cells. [3][4][5][6] There are few studies regarding PEDF expression in the skin, 7,8 and none in condyloma acuminatum. The aim of the present study, therefore, was to investigate SERPINF1 mRNA and PEGF protein levels in condyloma acuminatum and in healthy skin, using reverse transcription-polymerase chain reaction (RT-PCR) and Western blotting, respectively.…”
Section: Introductionmentioning
confidence: 99%